The Influence of Leadership Style, Work Discipline, and Motivation on Employee Performance at PT BNI KCU Rawamangun Jakarta - Shohiron, Shofi; Gopar, Ida Abdul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research was conducted at BNI KCU Rawamangun, East Jakarta City involving 43 employees as respondents. This research aims to explore the influence of leadership style, work discipline, and motivation on employee performance both partially and simultaneously. The method used in this research is quantitative. The research results show that leadership style partially has a significant effect on employee performance, with a calculated t-value of 2.875 which is greater than the t-table of 1.684, and a significance value (sig) of less than 0.05. Work discipline partially has a significant effect on employee performance, with a calculated t-value of 7.099 which is greater than the t-table of 1.684, and a significance value (sig) of less than 0.05. Motivation partially has a significant effect on employee performance, with a t-value of 3.456 which is greater than the t-table of 1.684 and a sig of less than 0.05. Simultaneously, leadership style, work discipline, and motivation have a significant effect on employee performance. The joint influence of leadership style, work discipline, and motivation on employee performance reaches 86%, while the remaining 14% is influenced by other variables. These findings offer a solid foundation for an in-depth understanding of the variables that influence the productivity of workers in the banking sector. The theoretical implications highlight crucial aspects that can be strengthened, while on the practical side, this research offers in-depth insights for financial institutions and industry players to design effective strategies and programs to improve the performance of their employees. This emphasizes the importance of adopting an effective leadership style, encouraging strong work discipline, motivating employees, and encouraging active participation in efforts to achieve company performance targets. This research was conducted at BNI KCU Rawamangun, East Jakarta City involving 43 employees as respondents. This research aims to explore the influence of leadership style, work discipline, and motivation on employee performance both partially and simultaneously. The method used in this research is quantitative. The research results show that leadership style partially has a significant effect on employee performance, with a calculated t-value of 2.875 which is greater than the t-table of 1.684, and a significance value (sig) of less than 0.05. Work discipline partially has a significant effect on employee performance, with a calculated t-value of 7.099 which is greater than the t-table of 1.684, and a significance value (sig) of less than 0.05. Motivation partially has a significant effect on employee performance, with a t-value of 3.456 which is greater than the t-table of 1.684 and a sig of less than 0.05. Simultaneously, leadership style, work discipline, and motivation have a significant effect on employee performance. The joint influence of leadership style, work discipline, and motivation on employee performance reaches 86%, while the remaining 14% is influenced by other variables. These findings offer a solid foundation for an in-depth understanding of the variables that influence the productivity of workers in the banking sector. The theoretical implications highlight crucial aspects that can be strengthened, while on the practical side, this research offers in-depth insights for financial institutions and industry players to design effective strategies and programs to improve the performance of their employees. This emphasizes the importance of adopting an effective leadership style, encouraging strong work discipline, motivating employees, and encouraging active participation in efforts to achieve company performance targets.